The environmental footprint of Holocene societies: a multi-temporal study of trails in the Judean Desert, Israel - Nir, Nadav; Davidovich, Uri; Ullman, Micka; Schütt, Brigitta; Stahlschmidt, Mareike C. (Frontiers in Earth Science, 2023)
The global distribution of footpaths and their inferred antiquity implies that they are widespread spatial and temporal anthropogenic landscape units. Arid environments are of special interest for investigating historically used footpaths, as older routes may preserve better due to minimal modern impact and slower pedogenic processes. Here we examine footpaths in the Judean Desert of the southern Levant, a human hotspot throughout the Holocene. We studied one modern and two archaeological footpaths (one attributed to the Early Bronze Age and one to the Roman period) using micromorphology, bulk samples laboratory analysis, and remote sensing. Field observations and color analysis indicate that footpaths in the studied arid limestone environment can result in brighter surface color than their non-path surroundings. Similar color changes are reflected using both laboratory analysis and high-resolution remote sensing, where the difference is also significant. Microscopically, the footpaths studied tend to be less porous and with fewer biogenic activities when compared to their non-path controls. However, the two ancient footpaths studied do exhibit minimal indicators of biogenic activities that are not detectable in the modern footpath sample. Our study shows that high-resolution remote sensing coupled with micromorphology, while using appropriate local modern analogies, can help to locate and assess both the environmental effect and the antiquity of footpaths.